2022
DOI: 10.1186/s13071-022-05198-7
|View full text |Cite
|
Sign up to set email alerts
|

Saliva collection via capillary method may underestimate arboviral transmission by mosquitoes

Abstract: Background Arthropod-borne viruses (arboviruses) impose a major health and economic burden on human populations globally, with mosquitoes serving as important vectors. Measuring the ability of a mosquito population to transmit an arbovirus is important in terms of evaluating its public health risk. In the laboratory, a variety of methods are used to estimate arboviral transmission by mosquitoes, including indirect methods involving viral detection from mosquito saliva collected by forced saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…This may result in an overestimation of b, because too few mosquitoes are considered capable of transmitting virus (n). The method of detecting virus in saliva has imperfect sensitivity (Gloria-Soria et al, 2022). This was also demonstrated by the animal in the low exposure group that did become viremic after exposure to mosquitoes without detectable viral particles in saliva.…”
Section: Discussionmentioning
confidence: 98%
“…This may result in an overestimation of b, because too few mosquitoes are considered capable of transmitting virus (n). The method of detecting virus in saliva has imperfect sensitivity (Gloria-Soria et al, 2022). This was also demonstrated by the animal in the low exposure group that did become viremic after exposure to mosquitoes without detectable viral particles in saliva.…”
Section: Discussionmentioning
confidence: 98%
“…aegypti. Saliva infection assays likely underrepresent transmission potential 65 , but our analyses of midgut and carcass infections suggest that Wolbachia infections will likely reduce DENV2 transmission.…”
Section: Wolbachia Infections Block Denv2 Replication and Disseminati...mentioning
confidence: 89%
“…However, the limited number of positive saliva samples detected may be influenced by the saliva collection technique or the presence of salivary gland infection barrier (SGIB) and SGEB (Gloria-Soria et al, 2016). Recent research has proposed that the presence of the virus in mosquito legs may be a more accurate predictor of transmission than the forced salivation method using a capillary tube (Gloria-Soria et al, 2022). Nevertheless, in our study, DER remained below 40%, requiring viral doses higher than those found in human viraemias to transmit the virus (Pinheiro et al, 1981;Long et al, 2011).…”
Section: Discussionmentioning
confidence: 99%